INCREASE THE LEVEL OF CAPITALIZATION OF NON-BANK CREDIT ORGANIZATIONS: https://doi.org/10.5281/zenodo.14292575 - Sariyev, Uygun (Science technology&Digital finance, 2024)
This article analyzes the problem of increasing the level of capitalization of non-bank credit organizations. Nonbank credit organizations contribute to economic development primarily by providing loans, consumer loans, and other financial services to small and medium-sized businesses. However, the level of capital resources and capitalization play an important role in the successful implementation of their activities. The article will look at how increased capitalization helps to ensure the financial stability of non-banking organizations, reduce risks and increase competitiveness.